Capacidades Dinâmicas no Agronegócio Sustentável: caminhos e desafios - Garcia, Renato de Mattos (2019)
Dynamic capabilities are ways of reallocating resources based on the context in which a company is in search of competitive advantage. They are based on the vision of resources (VBR) and are built from a deliberate learning trajectory (Zollo & Winter, 2003), when thought in the light of sustainability, it presupposes ways of transforming cleaner production into superior performance results. One of the most important sectors of the Brazilian economy today is Agribusiness, contributing to high export rates for fresh products. However, much is discussed about how much this sector contributes or hinders sustainable development in Brazil. Thus, the objective proposed in this work is to identify the dynamic capabilities for agribusiness sustainability in the light of the adjusted model of Cezarino et al. (2018). The study is qualitative and was developed through in-depth interviews with managers of agribusiness companies active in the Brazilian cerrado. The results obtained in the context of Brazilian agribusiness pointed out that the triad of strategic integration, culture and innovation are valid constructs, however the relationships of the production chain and innovations for the circular economy make up the essential competences for sustainable development in Brazil.